RIG‐I is required for VSV‐induced cytokine production by murine glia and acts in combination with DAI to initiate responses to HSV‐1. Issue 12 (3rd July 2015) - Crill, Emma K.; Furr‐Rogers, Samantha R.; Marriott, Ian
<x xml:space="preserve">Abstract</x> A defining feature of viral central nervous system (CNS) infection is the rapid onset of severe neuroinflammation. However, the mechanisms underlying glial responses to replicative neurotropic viruses are only now becoming apparent with the discovery of a number of cytosolic sensors for viral nucleic acids. We have described the expression by murine and human glial cells of two disparate pattern recognition receptors, retinoic acid inducible gene‐I (RIG‐I) and DNA‐dependent activator of interferon regulatory factors (DAI), receptors for viral RNA and DNA moieties, respectively. In the present study, we demonstrate the functional significance of RIG‐I expression in primary murine microglia and astrocytes. Our data indicate that murine glial immune responses to a model neurotropic RNA virus, vesicular stomatitis virus, are RIG‐I dependent and independent of levels of DAI expression or RNA polymerase III activity. In contrast, maximal glial inflammatory and antiviral responses to the DNA virus herpes simplex virus‐1 (HSV‐1) are dependent on the expression of both RIG‐I and DAI, and require RNA polymerase III activity. These findings indicate that the RNA sensor, RIG‐I, acts in parallel with DAI in an RNA polymerase III‐dependent manner to initiate glial responses to HSV‐1. We therefore suggest that RIG‐I plays a significant role in the detection of both RNA and DNA pathogens by microglia and astrocytes. GLIA 2015;63:2168–2180